Revisión y reivindicación de las poesías de José Iglesias de la Casa publicadas en la prensa: el caso del Diario de las musas - Noelia López-Souto (Cahiers de Civilisation Espagnole Contemporaine)
This work shows the importance of the press for the dissemination of poetry at the end of the 18th century and beginning of the 19th, as well as its study for a better understanding of the poetic output of the era. In particular, the article focuses on the case of Iglesias de la Casa, a Spanish author from the late 18th century and famous for his Poesías póstumas (1793), although towards the end of his life he had already published, some of those anacreontic, amorous-pastoral, and satirical poems in periodical format. By means of a critical methodology and newspaper archival research, this work reviews Iglesias' poetic work in the press and, specifically, his poetic corpus published during his lifetime, as well as his characterization according to the conditions that the medium required. Finally, the value of studying these poetic corpora in the press, specifically in the case of Iglesias, is considered because in authors from the 18th and 19th centuries, it often reveals unpublished or textual variants that allow us to delve deeper into the creative process behind those poems and their various testimonies.